A smart laboratory for the redevelopment of A.T.E.R. settlements in L'Aquila - Maria Cristina Forlani (Techne, 2012)
The research proposes the development of the heritage of social housing as a public experiment to measure up to the quality parameters required for the achievement of a ‘European model of the city.’ The goal is configuring a development that can return, or provide, the liveability to the settlements considered, conscious of the territorial reality characterized by widespread housing system and consistent with the evolving needs (social, economic and environmental) and the emerging socio-economic and environmental criticalities. The work is developed from knowledge of the settlement and the territorial system connected, as the basis for prefiguration of a scenario in which you identify a few privileged areas of action for the main urban and territorial dynamics, the management of ‘flows’, and new areas of discussion related to the problem of time, communication, mobility and logistics. You configure structural and managerial innovations (enhancement of territorial potentialities and integration of productive sectors; building cycle based on the recovery and rehabilitation). A ‘closed loop system’ where urban regeneration is powered and built from local resources.